Characterizing Cathepsin Activity and Macrophage Subtypes in Excised Human Carotid Plaques. Issue 4 (April 2016) - Abd-Elrahman, Ihab; Meir, Karen; Kosuge, Hisanori; Ben-Nun, Yael; Weiss Sadan, Tommy; Rubinstein, Chen; Samet, Yaacov; McConnell, Michael V.; Blum, Galia
Abstract : Background and Purpose—: Atherosclerosis is a leading cause of mortality worldwide, contributing to both strokes and heart attacks. Macrophages are key players in atherogenesis, promoting vascular inflammation and arterial remodeling through cysteine cathepsin proteases. We used a cathepsin-targeted activity-based probe in human carotid plaque to assess its diagnostic potential and evaluate macrophage subtypes ex vivo. Methods—: Carotid plaque specimens surgically removed during endarterectomy from 62 patients (age range, 38% female, 28% symptomatic) were graded pathologically as either stable (Grade 1) or unstable (Grade 2 or 3). A cathepsin activity-based probe was used to quantify individual cathepsins in plaque tissue and macrophage subtypes. Results—: Cathepsin B and S activities were increased in unstable carotid plaques. They were quantified using the probe to biochemically investigate individual cathepsins (Cathepsin B and S: 0.97 and 0.90 for grade 3 versus 0.51 and 0.59 for grade 1; P =0.006 and P =0.03 arbitrary units (AU), respectively). Higher cathepsin activity was observed in carotid plaques from symptomatic patients (Cathepsin B and S: 0.65 and 0.77 for asymptomatic, 0.99 and 1.17 for symptomatic; P =0.008 and P =0.005 AU, respectively). Additionally, it was demonstrated that M2 macrophages from unstable plaques express cathepsin activity 5-fold higher than M2 macrophages from stable plaques (25.52 versus 5.22; P =0.008 AU). Conclusions—: Targeting cathepsin activity in human carotid plaques may present a novel diagnostic tool for characterizing high-risk plaques. Novel cathepsin activity patterns within plaques and macrophage subpopulations suggest their involvement in the transition to active disease. Abstract : Supplemental Digital Content is available in the text.